Avaliaç\~ao dos conflitos do compartilhamento de postes entre os setores de distribuiç\~ao de energia e telecomunicaç\~oes - Bruna de Abreu Martins; Luis Claudio Kubota; Luiz Alexandre Moreira Barros; Mauricio Benedeti Rosa (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
This discussion paper seeks to contribute to the Brazilian urban development debate by analyzing the recent legislation that institutes the Casa Verde Amarela social housing program (CVA). Created in 2020, CVA arose from a provisory executive order (MP 996, of August 25) reformed on January 12, 2021, by federal law 14,118. This CVA analysis seeks to contribute to its operationalization in line with recognized rights and constitutional, legal, and binding principles present in international agreements to which Brazil is a signatory, particularly the 2030 Agenda (Sustainable Development Goals SDG) and the New Urban Agenda (NAU). This analysis focus on public policy management and its implementation, considering the structures of Brazilian urban development, both normative and political-social, and urbanistic. The evaluation carried out focuses on CVA management, seeking legal and operational instruments created even before the "program" formalization, in addition to regulations elaborated after and before. This prospective evaluation is necessary to present the CVA and its possible impacts on urban, public, and private managers.
Keywords: K23; K32; L94; L96; 330; infrastructure sharing; poles; energy; telecommunications